Factors Affecting Less Proficient Esl Learners’ Use Of Strategies For Language And Content Area Learning - Ismail, Rosemala (2008)

(untitled)
The purpose of this study was to explore the factors that affect language strategies of ESL learners and use of language strategies in content area learning. The study was guided by three research questions: 1) What are the personal, home and institutional factors affecting English language learning among the less-proficient university students and how they affect the respondents in their English language learning?; 2) What are the language learning strategies (LLS) used by these respondents in the language classroom and content area classroom?; 3) How do they employ language strategies in attending to content area subjects? The qualitative research design which employed the case study method was used in conducting the study. One case site consisting of a group of seven students from the Business Management and Accounting Faculty in Universiti Darul Iman Malaysia (UDM) in Terengganu, Malaysia was chosen. The pool of prospective respondents was chosen using purposive sampling technique. The selection of the respondents was based on the following criteria: 1) they were in their second semester of their studies; 2) they were studying in the ESL program; 3) they were also studying in the Business Management Program and 4) they scored 45 points and below for their English course at the end-of-first semester. The primary data collection technique employed in this case study was the interview. Observations were also made during the lectures and documents that include handouts and notes taken by the respondents were reviewed and analyzed to supplement the data collection. The data were analyzed according to categories and themes and the findings were presented according to each research question. The research questions provided a thematic analysis of the transcripts. Triangulation, peer examination and member check were subsequently used to validate the study. The findings showed that there were three contributing factors affecting students’ learning strategies and had been categorized as student factor, home factor, and institutional factor. In each category the research reported on what were considered by learners as facilitating factors and inhibiting factors. Facilitating factors promote motivation to learn the language while the inhibiting factors prohibit language learning. Furthermore, the themes of the language strategies acquired by the less-proficient students can be briefly categorized under two broad strategies: self-initiating and peer-based. It was also found that the teacher factor was an important influence on students’ motivation to learn about the language but not on the choice of language strategies used by the students. This suggests that language strategies may have been fossilized earlier, and teachers therefore need to instill in more direct and consistent ways on how new strategies for language learning and content area learning can be adopted. When learning their content area subjects, it was found that the students grappled with the content, and adopted strategies such as memorization, peer discussion and reference to seniors. They sought peers and seniors as sources of reference mostly to help clarify concepts which may be in English or Malay. The students showed low engagement in active production and discourse of ideas in English. In terms of theoretical and practical implications, this study had identified that there is a gap between the language skills the educators are providing the students in the English classroom and what they actually need to attend to in the content area learning. Students did not see the connection and usefulness of the language classroom and the role played by the language strategies in helping them with content area subjects particularly in helping them to understand, clarify, apply and extrapolate tasks given. In order to close the gap, this study has developed a model of an integrated approach to learning which combines the teacher factor, relevant and meaningful curriculum, and support amongst peers. The model is called the Integrated Content Area-Language Learning Strategies (ICALLS) model. This model is believed to be able to promote and upgrade not only the teaching of language but also to enhance the students’ content area subject learning.